Analysis of Computational Thinking Ability of Informatics Education Students - lobang, marisa enjelika marsanda; Sogen, Maria Magdalena Beatrice; Io, Reginaldis Jesika; Dae, Daniell Lakke; Ledoh, Pingky Kimberly (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Computational thinking (CT) is a systematic and logical problem-solving skil crucial in computer science education for effective problrm-solving. This research aims to analyze the computational thinking abilites of computer science education students, specifically in the aspects of problem identification, decomposition, abstracation, pattern recognition, and algorithms.The study utilized a mixed-methods approach (quantitative and qualitative) with questionnaires as the data collection instrument.The findings indicate that computer science education students possess a good basic CT ability,particularly in identifying problems and developing solution algorithms.however,there was variation in abilities regarding decomposition and abstraction,xhich still need improvement.These findings provide an important basic for developing more effective curricula and teaching methods to enhance students computational thinking skills..improved CT abilities are believed to increase students preparedness for the increasingly complex challenges of technology and the professional world. Computational thinking (CT) merupakan keterampilan berpikir sistematis dan logis yang sangat penting dalam dunia pendidikan informatika untuk memecahkan masalah secara efektif. Penelitian ini bertujuan untuk menganalisis kemampuan computational thinking mahasiswa Pendidikan informatika, khususnya dalam aspek identifikasi masalah, dekomposisi, abstraksi, pengenalan pola, dan algoritma. Metode penelitian yang digunakan adalah metode campuran kuantitatif dan kualitatif (mixed metod) dengan pendekatan , menggunakan kuesioner sebagai instrumen pengumpulan data. Hasil penelitian menunjukkan bahwa mahasiswa Pendidikan informatika memiliki kemampuan dasar CT yang baik, terutama dalam mengidentifikasi masalah dan Menyusun algoritma Solusi. Namun, terdapat variasi kemampuan pada aspek dekomposisi dan abstraksi yang masih perlu ditingkatkan. Temuan ini memberikan dasar penting bagi pengembangan kurikulum dan metode pembelajaran yang lebih efektif dalam mengasah kemampuan computational thinking mahasiswa. Peningkatan kemampuan CT diyakini dapat meningkatkan kesiapan mahasiswa dalam menghadapi tantangan teknologi dan dunia kerja yang semakin kompleks.